Presynaptic Aβ40 prevents synapse addition in the adult Drosophila neuromuscular junction - López-Arias, Begoña (PLoS One, 2017)
Complexity in the processing of the Amyloid Precursor Protein, which generates a mixture of βamyloid peptides, lies beneath the difficulty in understanding the etiology of Alzheimer’s disease. Moreover, whether Aβ peptides have any physiological role in neurons is an unresolved question. By expressing single, defined Aβ peptides in Drosophila, specific effects can be discriminated in vivo. Here, we show that in the adult neuromuscular junction (NMJ), presynaptic expression of Aβ40 hinders the synaptic addition that normally occurs in adults, yielding NMJs with an invariable number of active zones at all ages tested. A similar trend is observed for Aβ42 at young ages, but net synaptic loss occurs at older ages in NMJs expressing this amyloid species. In contrast, Aβ42arc produces net synaptic loss at all ages tested, although age-dependent synaptic variations are maintained. Inhibition of the PI3K synaptogenic pathway may mediate some of these effects, because western analyses show that Aβ peptides block activation of this pathway, and Aβ species-specific synaptotoxic effects persists in NMJs overgrown by over-expression of PI3K. Finally, individual Aβ effects are also observed when toxicity is examined by quantifying neurodegeneration and survival. Our results suggest a physiological effect of Aβ40 in synaptic plasticity, and imply different toxic mechanisms for each peptide species.